2013 2nd International Conference on Advances in Biomedical Engineering 2013
DOI: 10.1109/icabme.2013.6648832
|View full text |Cite
|
Sign up to set email alerts
|

Delta-fuzzy similarity entropy to discriminate healthy from sick fetus

Abstract: This paper deals with the discrimination between suffering and healthy fetuses, by means of a delta-fuzzy-similarity entropy. This new descriptor of complexity is based on the derivative of the fuzzy-similarity entropy. It was tested on fetal heart rate time-series and compared to the approximated and similarity entropies. The main outcome was the possibility to improve 10% the specificity and the sensitivity as compared to approximate entropy. This very good performance confirms that the new descriptor can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The straightforward comparison of the cross-diagonal values with the detected points forming the cross-diagonal lines obtained through the reference method, RP 2 , showed that (i) 27% out of 22% cross-diagonal points were detected in RP 3 , (ii) 13.3% out of 22% cross-diagonal points were detected in RP 4 , and (iii) 13% out of 22% cross-diagonal points were detected in RP 5 .…”
Section: Quantitative Evaluation Of Sojourn Point Reductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The straightforward comparison of the cross-diagonal values with the detected points forming the cross-diagonal lines obtained through the reference method, RP 2 , showed that (i) 27% out of 22% cross-diagonal points were detected in RP 3 , (ii) 13.3% out of 22% cross-diagonal points were detected in RP 4 , and (iii) 13% out of 22% cross-diagonal points were detected in RP 5 .…”
Section: Quantitative Evaluation Of Sojourn Point Reductionmentioning
confidence: 96%
“…Complexity analysis of biomedical time series by means of various descriptors including, but not limited to, fractal dimension [1], multi-fractal spectra [2], and entropies [3][4][5] is quantitative and currently standard practice.…”
Section: Introductionmentioning
confidence: 99%
“…SD that measures the amount of RQA i dispersion from its average value is given as follows: (8) where N is the total number of FHRs used.…”
Section: Statistical Tools For Evaluating the Discriminationmentioning
confidence: 99%
“…Some of these tools were quantitative, such as the entropy (En) analysis and types including, but not limited to, the approximated entropy, sample entropy, fuzzy entropy and recently n-order entropy [4,5,7,8,11]. Other methods were qualitative such as the Recurrence Plots (RPs) and their corresponding Recurrence Quantification Analysis (RQA) [2,3,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation